Application of the Intervention Mapping Framework to Develop an Integrated Twenty-First Century Core Curriculum-Part 1: Mobilizing the Community to Revise the Masters of Public Health Core Competencies - Rita DeBate; Jaime A. Corvin; Kate Wolfe-Quintero; Donna J. Petersen (Frontiers Media S.A., 2017)
Twenty-first century health challenges have significantly altered the expanding role and functions of public health professionals. Guided by a call from the Association of Schools and Programs of Public Health's (ASPPH) and the Framing the Future: The Second 100 Years of Education for Public Health report to adopt new and innovative approaches to prepare public health leaders, the University of South Florida College of Public Health aimed to self-assess the current Masters of Public Health (MPH) core curriculum with regard to preparing students to meet twenty-first century public health challenges. This paper describes how Intervention Mapping was employed as a framework to increase readiness and mobilize the COPH community for curricular change. Intervention Mapping provides an ideal framework, allowing organizations to access capacity, specify goals, and guide the change process from curriculum development to implementation and evaluation of competency-driven programs. The steps outlined in this paper resulted in a final set of revised MPH core competencies that are interdisciplinary in nature and fulfill the emergent needs to address changing trends in both public health education and challenges in population health approaches. Ultimately, the competencies developed through this process were agreed upon by the entire College of Public Health faculty, signaling one college's readiness for change, while providing the impetus to revolutionize the delivery of public health education at the University of South Florida.